PERSEPSI PERAWAT DI TEMPAT PRAKTIK MANDIRI KEPERAWATAN TERHADAP POLA HIDUP SEHAT DAN PENCEGAHAN HIPERTENSI - Claudia, Revalina Ayu; Koesrini, Juliati (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2025)
Hypertension is one of the leading non-communicable diseases with a steadily increasing incidence, often associated with unhealthy lifestyle habits. Nurses play a strategic role in preventing hypertension through the promotion of healthy living, particularly in Independent Nursing Practice Centers (TPMK) that directly serve the community. This study aims to explore nurses’ perceptions at TPMK regarding the implementation of a healthy lifestyle and hypertension prevention efforts. This research employed a qualitative descriptive approach with purposive sampling involving nurses working in TPMK. Data were collected through in-depth interviews, observations, and documentation, and analyzed using Miles and Huberman’s interactive model. The results revealed that nurses generally have a positive perception of the importance of healthy lifestyles in preventing hypertension; however, implementation remains challenged by low public awareness and time limitations in service delivery. The study concludes that nurses hold significant potential as agents of behavioral change in the community, and policy support as well as continuous training are essential to optimize this role.